The effectiveness of Jicama Yogurt (Pachyrhizus erosus) to Lipid Profile and Triglyceride Levels - Hasneli Hasneli; Kasmiyetti Kasmiyetti; Fitria Mushollini; Susi Rahmayeni (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2022)
ABSTRACTBackground: Cardiovascular disease is the number one cause of death in the world. One of the causes is hypercholesterolemia. The management of hypercholesterolemia can be done through non-pharmacological efforts by consuming hypocholesterolemic foods, including jicama and probiotic drinks. Probiotic and jicama drinks contain active compounds inulin and lactic acid bacteria which can control total cholesterol levels.Objectives: to determine the effectiveness of jicama yogurt probiotics on lipid profile and trygliceride levels of hypercholesterolemic employees of the Campus I Health Polytechnic of the Ministry of Health Padang.Methods: This study used a quasi-experimental study with pre-posttest design. The sample was 18 people from the Campus I Health Polytechnic of the Ministry of Health Padang with hypercholesterolemia, the study was conducted in January - November 2019. Respondents were given 120 ml of jicama yogurt probiotic for 14 days. Analysis using the dependent t-test.Results: The results showed that the average initial total cholesterol level was 218.33 mg/dL, HDL 51.11 mg/dL, LDL 145.11 mg/dL, triglycerides 111.39 mg/dL and the final total cholesterol level was 217.78 mg/dL, HDL 56.67 mg/dL, LDL 139.56 mg/dL, Triglycerides 109.22 mg/dL. The average reduction in total cholesterol levels in the group was 0.56 mg/dL, LDL was 5.56 mg/dL, triglycerides 2.17 mg/dL, an average increase in HDL levels was 5.56 mg/dL. The results of statistical tests showed that there was a significant difference between HDL levels before and after intervention (p 0.05).Conclusion: Jicama yogurt probiotics are more effective in positively modifying the lipid profile levels. Jicama yogurt probiotic can be used as an alternative complementary therapy for hypercholesterolemic sufferers.KEYWORDS: Hypercholesterolemia; jicama; Lipid profile; probiotics